The tax system in Sweden - Norr, Martin; Sandels, Claes; Hornhammer, Nils G.; Stockholms enskilda bank, ab. (Stockholm, Stockholms Enskilda Bank, 1969)
This pamphlet brings up to date the information contained in Taxation in Sweden.
Includes bibliographical references.
oif 26/02/2019
Loans
Keywords: Income tax